Should Benzodiazepines and Anticonvulsants Be Used During Electroconvulsive Therapy?: A Case Study and Literature Review. Issue 4 (December 2017) - Tang, Victor M.; Pasricha, Akash N.; Blumberger, Daniel M.; Voineskos, Daphne; Pasricha, Suvercha; Mulsant, Benoit H.; Daskalakis, Zafiris J.
Abstract : Objective: This study aims to investigate the clinical effects of benzodiazepines or anticonvulsant use during a course of electroconvulsive therapy (ECT). Method: A case report study of a patient who received ECT with and without concomitant flurazepam and pregabalin is presented. The literature on the use of benzodiazepines and anticonvulsants during ECT is reviewed. Results: A woman with treatment resistant depression received a course of ECT while taking flurazepam and pregabalin, but seizures were of short duration and symptomatic improvement was minimal. After discontinuation of flurazepam and pregabalin, a course of right unilateral ultrabrief ECT was associated with adequate seizures and remission of depression and suicidal ideation. Our literature review suggests that benzodiazepines decrease seizure duration, but most evidence shows no association with increased seizure threshold. One prospective RCT and 3 large retrospective studies found that benzodiazepines compromise the efficacy of unilateral but not bilateral ECT. Regarding anticonvulsants, several studies had varied and contradictory results on their effect on seizure duration and seizure threshold. Of the 2 large retrospective studies and 3 RCTs, only 1 retrospective study showed that anticonvulsants decrease the efficacy of ECT. Conclusions: Judicious assessment of all medications used in combination with ECT is recommended. Overall, published studies suggest that benzodiazepines and anticonvulsants impact the clinical outcomes of ECT less than what would be expected given their pharmacologic effects. However, there are significant gaps in the literature, including a lack of study on suprathreshold stimulation of right unilateral ECT and the possibility of a greater effect with higher medication doses.